Voice impersonation detection using LSTM based RNN and explainable AI - Barua, Kawshik; Rahim, Abdur; Parizat, Prantozit Saha; Noor, Md.Asad Uzzaman; Jannah, Miftahul (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.